Internet Gaming Disorder among Undergraduate Health Sciences Students in the Pokhara Valley: a Cross-Sectional Study - Shahi, Sujata; Baral, Yuba Raj; Mishra, Durga Khadka (International Journal of Occupational Safety and Health, 2023)
Introduction: Internet Gaming Disorder (IGD) is an emerging public health impact of technological advancement and globalization. This study was conducted to assess the prevalence and factors associated with IGD among Undergraduate Health Sciences students. Methods: A web-based cross-sectional study was conducted during the period of November to July 2020. A total of 412 college students from Undergraduate Health Sciences colleges of Pokhara Metropolitan city in Gandaki province, Nepal were enrolled. Online google forms were sent to all the eligible students through email and other social media sites like Facebook with the help of the coordinator and class representative. Collected data were analyzed using SPSS IBM v.22 Results: The finding of the study shows that the prevalence of Internet Gaming Disorder among Undergraduate Health Sciences students was 7.1%. Sex (p=0.027), Loneliness level at home (p=0.019), number of close friends (p<0.001), types of game (p<0.001), time spent on playing game (p<0.001), and, type of gamer (p<0.001) were the factors associated with Internet Gaming Disorder among the participants. Conclusion: Sex of the participants, loneliness level at home, number of close friends, types of game, time spent on the gameplay, and type of gamer are the contributing factors for developing Internet Gaming Disorder. It is important to focus on these factors to address Internet Gaming Disorder and its psychological health effects.